Generalized equations - Magreñán, Á. Alberto; Argyros, Ioannis K (Contemporary study of iterative methods: convergence, dynamics and applications, 2021)
In this chapter we present some developments for the local convergence of Newton's method. Some special cases and a numerical example illuminating the theoretical results are also presented.
Capítulo del libro "Contemporary study of iterative methods: convergence, dynamics and applications"
Keywords: generalized equations; Newton's method; local convergence; WOS(2)